Breaking barriers: the legacy and voices of women pioneers in accounting education in Peru - Chávez-Díaz, Jorge M.; Monterroso-Unuysuncco, Nilda Irma; De Velazco-Borda, Jorge; Aquiño-Perales, Laura; Villagómez-Chinchay, Juan Alberto; Pecho-Rafael, Mélida H. (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study examines the contributions of pioneering women in Peruvian accounting, both in scientific research and university teaching, in a historically male-dominated field. The research aims to highlight their academic impact and professional legacy. A qualitative approach was employed, utilizing the collective biography method and a phenomenological perspective. The study analyzed historical undergraduate and graduate theses from the Universidad Nacional Mayor de San Marcos (UNMSM) and conducted interviews with five distinguished female accounting professors. The findings reveal that these women made significant contributions in key areas such as financial auditing, management accounting, and environmental auditing, demonstrating adaptability and ethical commitment. In the educational sphere, participants emphasized their transformative teaching experiences, dedication to students, and the challenges posed by technology and social changes. The study concludes that these pioneers not only shaped the evolution of accounting education but also left a lasting legacy of academic and social engagement. The research underscores the need for gender equity policies and continuous technological adaptation in accounting education. These findings have practical implications for promoting diversity in academia and ensuring inclusive participation in the professional development of future generations.